Decoloration of Azo Dye Sunset Yellow by a Coaxial Insulated-Rod-to-Cylinder Underwater Streamer Discharge System - 温小琼 王明 丁振峰 刘贵师 (Plasma science & technology, 2012)
A coaxial insulated-rod-to-cylinder underwater streamer discharge system capable of injecting plasma into a large volume of water was developed and employed to decolorize azo dye sunset yellow. The rod type anode was covered by an insulator tube with a wall thickness of 0.4 mm. A series of slits with a width of 20 μm to 80 μm and a length of about 4 mm were cut onto the wall of the insulator tube. Depending on the solution conductivity, a cylindrical discharge region with a length of 60 mm and a wall thickness of 5 mm to 11 mm forms in the reactor. The influence of the solution conductivity, pH and pulse frequency on the decoloration of sunset yellow was investigated. The results show that the solution conductivity has little effect, while the solution pH and the pulse frequency have significant influence on the decoloration rate of sunset yellow. The decoloration rate of sunset yellow is increased with the increase in pulse frequency. A lower pH in solution promotes the decoloration of sunset yellow while a higher pH inhibits it.